Upaya Meningkatkan Kualitas UMKM Desa Penusupan Melalui Program KKN Kelompok 66 Kegiatan Pelatihan Digitalisasi UMKM - Khaerul, Khaerul Rizal; Pujianto, Aris; Burhanudin, Muhammad (Jurnal Pengabdian Inovasi Masyarakat Indonesia, 2023)
The aim of this digital marketing training and mentoring activity is to improve the quality of UMKM in terms of utilizing digital platforms. As well as providing alternative livelihood options for participants or new sources to increase their income. The target of the training and mentoring are UMKM actors in Penusupan village, Randudongkal sub-district with a total of 20 participants who all have mobile phones that support digital marketing applications. The method used in digital marketing training and assistance is the lecture or socialization method and direct practice. From the digital marketing training, it can be concluded that very Google business skills and UMKM product labeling are very important to build and can provide skills to trainees in entrepreneurship. From this training and mentoring activity, 20 accounts were produced which could become digital marketing tools or facilities. In addition, a sharing group was also formed which is useful as a forum for encouragement and building bonds of brotherhood, cohesiveness between participants and sharing of problems encountered and solutions that can be discussed together between training participants and digital marketing assistance. Hopefully this digital marketing training and assistance will be useful and can increase knowledge, abilities and skills in terms of digital marketing.